The Role Of Flight Test Data Analysis In Development Flight Testing - Khasyofi, M (International Journal of Aviation Science and Engineering - AVIA, 2023)
Flight test purposes is to evaluate aircraft design and performance. Nature of flight test are hazardous and expensive so that it have to be planned well to ensure safety and effectiveness of the mission. Any data obtained from flight test must be utilized to get comprehensive evaluation of the aircraft characteristic. Flight test data play central role in aircraft development. As part of flight test team and flight test program, data analysis support aircraft designer to evaluate flight test data, data reduction, and determine the quality of flight test data. This paper described flight test data processing and flight test data analysis role duringflight test program from industry perspective. Flight test activity or flight test program start with the purpose whether for experimental, development and certification or production. Flight test program activity can be divided 3 phase: flight planning and preparation, flight test execution and flight test reporting. During flight test execution and flight test reporting, test data have to be process, distribute, and use properly. Data from aircraft and flight instrumentation wereprocess from raw data format to engineering unit. Data noise and error during flight test influenced by atmosphere condition, instrumentation, experience etc. Using several method in data reduction process, this error could be minimized as possible. Technology information make data processing and analysis process faster and more efficient. Some example in this paper came from industrial perspective during development new type design aircraft in IndonesianAerospace. Case example from this paper based on experiences during development and certification N219. For other aircraft case it may be more complicated or simple. Development of technology such as computation, electronic, and communication bring new method in data analysis. As digital technology increase amount of data and sensor capability to produce highresolution data make big data analytic should be considered as solution to improving data analytic capability in flight testing.